Cranial base topology and basic trends in the facial evolution of Homo. Issue 91 (February 2016) - Bastir, Markus; Rosas, Antonio
Abstract: Facial prognathism and projection are important characteristics in human evolution but their three-dimensional (3D) architectonic relationships to basicranial morphology are not clear. We used geometric morphometrics and measured 51 3D-landmarks in a comparative sample of modern humans ( N  = 78) and fossil Pleistocene hominins ( N  = 10) to investigate the spatial features of covariation between basicranial and facial elements. The study reveals complex morphological integration patterns in craniofacial evolution of Middle and Late Pleistocene hominins. A downwards-orientated cranial base correlates with alveolar maxillary prognathism, relatively larger faces, and relatively larger distances between the anterior cranial base and the frontal bone (projection). This upper facial projection correlates with increased overall relative size of the maxillary alveolar process. Vertical facial height is associated with tall nasal cavities and is accommodated by an elevated anterior cranial base, possibly because of relations between the cribriform and the nasal cavity in relation to body size and energetics. Variation in upper- and mid-facial projection can further be produced by basicranial topology in which the midline base and nasal cavity are shifted anteriorly relative to retracted lateral parts of the base and the face. The zygomatics and the middle cranial fossae act together as bilateral vertical systems that are either projected or retracted relative to the midline facial elements, causing either midfacial flatness or midfacial projection correspondingly. We propose that facial flatness and facial projection reflect classical principles of craniofacial growth counterparts, while facial orientation relative to the basicranium as well as facial proportions reflect the complex interplay of head-body integration in the light of encephalization and body size decrease in Middle to Late Pleistocene hominin evolution. Developmental and evolutionary patterns of integration may only partially overlap morphologically, and traditional concepts taken from research on two-dimensional (2D) lateral X-rays and sections have led to oversimplified and overly mechanistic models of basicranial evolution.